THEME: ASSESSMENT AND EVALUATION IN INTENSIVE LANGUAGE TEACHING - Safarova Dildora; Haqberdiyev Shahzod; Kubayev Javlon (Ustozlar uchun, 2025)
Assessment and evaluation play a crucial role in intensive language teaching, ensuring learners’ progress and curriculum effectiveness. These processes include formative and summative assessments, standardized testing, self-assessment, and peer evaluation. Intensive language programs require continuous monitoring to adapt teaching strategies and enhance student engagement. This article explores key assessment methods, challenges, and best practices in evaluating language proficiency. Properly designed assessments motivate learners, provide valuable feedback, and contribute to achieving linguistic fluency in a shorter timeframe.